Effect of continuing versus stopping pre-stroke antihypertensive agents within 12 h on outcome after stroke: A subgroup analysis of the efficacy of nitric oxide in stroke (ENOS) trial. (February 2022) - Woodhouse, Lisa J.; Appleton, Jason P.; Scutt, Polly; Everton, Lisa; Wilkinson, Gwenllian; Caso, Valeria; Czlonkowska, Anna; Gommans, John; Krishnan, Kailash; Laska, Ann C.; Ntaios, George; Ozturk, Serefnur; et al.
Summary: Background: It is not known whether to continue or temporarily stop existing antihypertensive drugs in patients with acute stroke. Methods: We performed a prospective subgroup analysis of patients enrolled into the Efficacy of Nitric Oxide in Stroke (ENOS) trial who were randomised to continue vs stop prior antihypertensive therapy within 12 h of stroke onset. The primary outcome was functional outcome, assessed with the modified Rankin Scale at 90 days by observers blinded to treatment assignment, and analysed with ordinal logistic regression. Findings: Of 4011 patients recruited into ENOS from 2001 to 2014, 2097 patients were randomised to continue vs stop prior antihypertensive treatment, and 384 (18.3%, continue 185, stop 199) were enrolled within 12 h of ictus: mean (SD) age 71.8 (11.8) years, female 193 (50.3%), ischaemic stroke 342 (89.1%) and total anterior circulation syndrome 114 (29.7%). As compared with stopping, continuing treatment within 12 h of onset lowered blood pressure by 15.5/9.6 mmHg ( p <0.001/<0.001) by 7 days, shifted the modified Rankin Scale to a worse outcome by day 90, adjusted common odds ratio (OR) 1.46 (95% CI 1.01–2.11), and was associated with an increased death rate by day 90 (hazard ratio 2.17, 95% CI 1.24–3.79). Other outcomes (disability - Barthel Index, quality of life - EQ-visual analogue scale, cognition - telephone mini-mental state examination, and mood - Zung depression scale) were also worse with continuing treatment. Interpretation: In this pre-specified subgroup analysis of the large ENOS trial, continuing prior antihypertensive therapy within 12 h of stroke onset in a predominantly ischaemic stroke population was unsafe with worse functional outcome, disability, cognition, mood, quality of life and increased death. Future studies assessing continuing or stopping prior antihypertensives in the context of thrombectomy are awaited. Funding: ENOS was funded by the UK Medical Research Council (G0501797), and Bupa, and supported by the Stroke Association.